Energy Expenditure as a Function of Activity Level After Spinal Cord Injury: The Need for Tetraplegia-Specific Energy Balance Guidelines - Shea, Jessie R.; Shay, Barbara L.; Leiter, Jeff; Cowley, Kristine C. (Frontiers in Physiology, 2018)
The World Health Organization recognizes obesity as a global and increasing problem for the general population. Because of their reduced physical functioning, people with spinal cord injury (SCI) face additional challenges for maintaining an appropriate whole body energy balance, and the majority with SCI are overweight or obese. SCI also reduces exercise capacity, particularly in those with higher-level injury (tetraplegia). Tetraplegia-specific Caloric energy expenditure (EE) data is scarce. Therefore, we measured resting and exercise-based energy expenditure in participants with tetraplegia and explored the accuracy of general population-based energy use predictors. Body composition and resting energy expenditure (REE) were measured in twenty-five adults with tetraplegia (C4/5 to C8) and in a sex-age-height matched group. Oxygen uptake, carbon dioxide production, heart rate, perceived exertion, and exercise intensity were also measured in 125 steady state exercise trials. Those with motor-complete tetraplegia, but not controls, had measured REE lower than predicted (mean = 22% less, p<0.0001). REE was also lower than controls when expressed per kg of lean mass. Nine had REE below 1200 kcal/day. We developed a graphic compendium of steady state EE during arm ergometry, wheeling and hand-cycling. This compendium is in a format that can be used by persons with tetraplegia for exercise prescription (Calories, at known absolute intensities). EE was low (55–450 kcal/hr) at the intensities participants with tetraplegia were capable of maintaining. If people with tetraplegia followed SCI-specific activity guidelines (220 minutes/week) at the median intensities we measured, they would expend 563 - 1031 kcal/wk. Participants with tetraplegia would therefore require significant time (4 to over 20 hours) to meet a weekly 2000 kcal exercise target. We estimated total daily EE for a range of activity levels in tetraplegia and compared them to predicted values for the general population. Our analysis indicated that the EE values for sedentary through moderate levels of activity in tetraplegia fall well below predicted sedentary levels of activity for the general population. These findings help explain sub-optimal responses to exercise interventions after tetraplegia, and support the need to develop tetraplegia-specific energy-balance guidelines that reflects their unique EE situation.